THE INFLUENCE OF SOCIAL MEDIA MARKETING ACTIVITIES, PERCEIVED VALUE, AND CUSTOMER EXPERIENCE ON SKINCARE CUSTOMER BEHAVIOR THROUGH RELATIONSHIP QUALITY - Gilang Pratama Hafidz; Siti Solehah Rahmah Tunisa (Jurnal Ekonomi, 2023)
The purpose of this study was to prove the direct and indirect effect on repurchase intention, loyalty intention and participation in skincare products. Further factors can be seen in the variables Social Media Marketing Activity, Perceived Value, and Customer Experience. This type of research was quantitative using a purposive sampling technique which was distributed via questionnaire to 295 skincare consumer respondents aged 17-45 years in the Bekasi area. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this study indicate that the variable Perceived Value has the greatest direct influence on Relationship Quality followed by Customer Experience and Social Media Marketing Activity. Then, Relationship Quality has the greatest indirect effect on the relationship between Perceived Value and Participation Intention, Repurchase Intention and Loyalty Intention. This research contributes to companies to focus more on the perceived value and customer experience. The results of this study suggest to future researchers to expand the research area, extend the duration of the research and conduct focus group discussions.